Stereotactic body radiation therapy for stage I non-small cell lung carcinomas: Moderate hypofractionation optimizes outcome. (December 2018) - Menoux, I.; Antoni, D.; Truntzer, P.; Keller, A.; Massard, G.; Noël, G.
Highlights: Local, regional and metastatic control rates at 2 years were respectively 94%, 95% and 81%. Overall survival rate at 2 years was 64%. These results are comparable with the main prospective studies. With 61.5% of radiation pneumonitis, mainly asymptomatic, and 4% of rib fracture, it is a well-tolerated treatment. Hypofractionation was associated with better outcome and tolerance. Abstract: Objectives: In case of inoperability or refusal of surgery, stereotactic body radiation therapy (SBRT) is the most effective treatment for a stage I non-small cell lung carcinoma (NSCLC). The results obtained by this irradiation technique are considerably superior to those observed in the time of conventional 3D irradiation and its toxicities are much less important, which makes it possible in elderly patients, or those presenting cardio-pulmonary comorbidities and a poor perfomance status. Materials and methods: This study is a retrospective analysis of 90 patients who underwent SBRT for a stage I NSCLC between 2010 and 2015. Its purpose is to describe its effectiveness in term of overall survival (OS), specific survival (SS), local control (LC), regional control (RC) and metastatic control (MC) as well as their prognostic factors, and its tolerance. Results: LC, RC, MC as well as OS and SS rate at 4 years were comparable to the main prospective studies, respectively 89%, 92%, 70%, 33% and 66%. No LC prognostic factor could be identified. Radiation pneumonitis was observed with a rate of 61.5%, of which 56% were asymptomatic, and 4% of the patients had a rib fracture. Conclusions: SBRT is an efficient and well-tolerated treatment for stage I non-small cell lung carcinomas